Pengaruh Pemahaman Agama Dan Kepercayaan Muzakki Terhadap Minat Membayar Zakat Di Badan Amil Zakat Nasional (Baznas) - Ulfa Nurul Huda (Tamaddun Ummah (JTU), 2022)
Understanding of religious teachings can be assessed as a stimulus that has an impact on one's actions. If someone understands the teachings of religion in this case regarding zakat, then he understands the obligation to pay zakat when it reaches the nisab and haul. And then the obligatory zakat called muzakki chooses and trusts the place of distribution of their zakat funds so that they are right on target and evenly distributed, which will later affect the interest in paying zakat in BAZNAS Dumai City. This research was conducted with the aim of knowing the influence of religious understanding and belief of Muzakki on the interest in paying Zakat at the National Zakat Agency (BAZNAS) Dumai City. This study uses a quantitative method approach, the data used in this study are primary data obtained through distributing questionnaires to 99 respondents. Data analysis used Multiple Linear Regression Analysis with the help of SPSS 16.0 Windows Software. The results showed that the understanding of religion and muzakki beliefs together had a positive and significant influence on the interest in paying zakat in BAZNAS Dumai City with a contribution of 21.5%. Partially muzakki trust gives a positive and significant contribution to the interest in paying zakat in BAZNAS Dumai City.